A study on contrastive rhetoric in English writing and the myside bias / Atiyeh Kamyabi Gol - Gol, Atiyeh Kamyabi (2012)
One effective method for conveying one’s thoughts and ideas is through writing. Having the ability to write effectively is important to both achieve and also to demonstrate academic success (Leki and Carson, 1994). Many scholars believe that cultural backgrounds play a vital role in how an individual writes. With the growing number of Iranian students studying overseas, it is necessary to see whether the Persian rhetorical culture does in fact influence students' English writing. In this study, the researcher aims to investigate the style differences between English and Persian writing and to determine whether participating Iranian EFL students transfer Persian writing cultural norms to their English argumentative writings. Also, both students’ and teachers’ perspectives on the most problematic areas of English writing will be studied. The presence of myside bias was also considered in the writings. Data for the study was collected through two argumentative essays (Persian and English). The results were triangulated through the use of a questionnaire and interview. The findings support the contrastive rhetoric theory in that the students’ L1 does influence the way they write in L2. The results show that there is a great possibility of transfer from the participants’ L1 into L2 in the areas of number of topic sentences per paragraph, and also figurative language usage. The findings also reveal the possibility of backward transfer in the area of position of thesis statement. The results also indicate a mismatch between the teachers and students’ perception of the most problematic areas in English writing. Traces of myside bias were also found in both argumentative essays.